ANALISIS STRATEGI GURU DALAM PEMBENTUKAN KARAKTER PEDULI LINGKUNGAN SISWA KELAS I DI SEKOLAH DASAR NEGERI 96 PALEMBANG - Deswita Aulia Nasution (JGK (Jurnal Guru Kita), 2023)
Analysis of Teacher Strategies In The Formation Of Environmental Care Character For Grade I Students At 96 Palembang State Elementary Schools. A strong character is a prerequisite to be a winner in the current and future competition field. The educational environment is believed to be a good place for the growth of students' character. This research is motivated by the problems of students who are less concerned about the surrounding environment. This study aims to describe what strategies are given by the teacher in the formation of the environmental care character of class I students. This research method uses qualitative methods. The subjects in this study were grade i teachers, school principals, and 6 grade I students at 96 Palembang Elementary School. Data collection techniques used are in the form of observation, interviews, and documentation. The results of this study indicate that the teacher's strategy in forming the character of caring for the environment in grade I students uses a good strategy and is in accordance with the indicators of the strategy for forming the character of caring for the environment which is the reference for researchers in this study. The indicator of strategy that is used as a reference for the author is exemplary, habituation, and instilling or enforcing discipline in students.